The Multifaceted Roles of RCC1 in Tumorigenesis - Ren, Xuanqi; Jiang, Kai; Zhang, Feng (Frontiers in Molecular Biosciences, 2020)
RCC1 is the only known guanine nucleotide exchange factor for Ran. RCC1 establishes a RanGTP concentration gradient by combining with chromatin and Ran, thereby participating in a series of cellular physiological activities. In this review, we discuss the structure of RCC1 and its combination with chromatin and Ran through its unique structure and describes how RCC1 affects the formation and function of nuclear envelope, spindle formation and nuclear transport. It also focuses on the impact of RCC1 on the cell cycle during tumorigenesis and the research progress of RCC1 in different tumors in recent years.